Effect of Time of Fruit Collection on the Seed Germination of Fraxinus xanthoxyloides (Wall. Ex G. Don) DC - Negi, P. S.; Sharma, Sandeep (Indian Forester, 2015)
An experimental trial was conducted to study the effect of time of fruit collection on the germination of Fraxinus xanthoxyloides seeds-an important lesser known tree species of cold desert area. The seeds of Fraxinus xanthoxyloides were collected on 15 days interval (Fortnightly basis) starting from 1st September, 2007 to 15th December, 2007 and were subjected to germination testing without any pre-sowing treatments. Significant differences were observed in germination percentage, moisture content of samaras and seeds of Fraxinus xanthoxyloides seeds collected during different collection period. Seed collected during second fortnight of October recorded maximum 26.67 per cent germination followed by 24.00 per cent in seeds collected during first fortnight of November and 23.33 per cent germination in seeds collected during first fortnight of October. Seeds collected during first fortnight of December recorded minimum 6.67 per cent germination. Optimum time of seed collection in Fraxinus xanthoxyloides is found to be between first fortnight of October and first fortnight of November.